PROCESS AND SYSTEMS Scenario-based design for a hospital setting: An exploratory study of opportunities and barriers for personal health records usage. Issue 2 (2020) - Subbe, Christian P; Pearson, Nick; Wischhusen, Stephanie; Hibbs, Richard; Wright, Sarah; Xenou, Maria
No abstract available